The Cytochromes of Prototheca zopfii - Epel, B. L. (1970)
The respiratory pigments of Prototheca zopfii include seven cytochromes: two c-type cytochromes, a soluble c(549) and a membrane bound c(551); three b-type cytochromes, b(555), b(559) and b(564); and cytochromes a and a(3). Cytochromes a and a(3) could be resolved spectrally in the α-band region by reducing the cells in the presence of methanol and cyanide. Methanol shifted the absorption maximum of cytochrome a from 598 to 603 nanometers and permitted dithionite (or substrate) to reduce the cyanide-cytochrome a(3) complex to give a well defined 595-nanometer absorption band. Methanol did not interfere with CO binding by cytochrome a(3), and CO did not alter the methanol effect on cytochrome a. Azide and cyanide, which partially inhibited exogenous respiration, stimulated endogenous respiration. Frozen steady states of the electron transport chain in the presence of cyanide and azide indicated that the stimulation by these inhibitors was due to an increased autooxidation of one of the b-type cytochromes, possibly b(564).